2017
DOI: 10.33899/ijvs.2017.145608
|View full text |Cite
|
Sign up to set email alerts
|

Femur fractures and treatment options in 20 dogs admitted to our clinic from January 2013 to December 2015

Abstract: The aim of the present study was to evaluate treatment of 20 dogs with femur fractures. Twenty (20) dogs with different ages, breeds, and gender admitted to the clinic of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
2
6
1
Order By: Relevance
“…Furthermore, fractures at the femoral shaft showed a higher incidence rate (3 versus 1) compared to other parts of the bone. In addition, the occurrence rate of transverse/oblique fractures (54.1% & 30.6% respectively) were recorded to be higher compared to comminuted (15.3%) ones, these results were found in accordance with previous reports of ( Tercanlioglu and Sarrierler, 2009;Shiju et al, 2011;Ben Ali, 2013;Abd El Raouf et al, 2017). We suggested that the anatomical characteristics of the femur and its inclined position within the animal's body make it liable to excessive stress more than other long bones other than the humerus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, fractures at the femoral shaft showed a higher incidence rate (3 versus 1) compared to other parts of the bone. In addition, the occurrence rate of transverse/oblique fractures (54.1% & 30.6% respectively) were recorded to be higher compared to comminuted (15.3%) ones, these results were found in accordance with previous reports of ( Tercanlioglu and Sarrierler, 2009;Shiju et al, 2011;Ben Ali, 2013;Abd El Raouf et al, 2017). We suggested that the anatomical characteristics of the femur and its inclined position within the animal's body make it liable to excessive stress more than other long bones other than the humerus.…”
Section: Discussionsupporting
confidence: 91%
“…It usually occurs as a result of violent trauma with a vehicular accident, gunshot injuries, and falls or occasionally due to pathologic diseases Surgery because of primary or metastatic bone tumors. It can result in both life-threatening injuries, severe and permanent disability (Gadallah et al, 2009;Fossum et al, 2013;Jain et al, 2018) Among different breeds of dogs, femoral fractures commonly occur in German shepherds (85%), Doberman pinscher (5%), and White Griffon (5%) (Abd El Raouf et al, 2017). It occurs mostly at the proximal or distal physis in immature dogs while in mature animals metaphyseal and diaphyseal fractures are the most frequently recorded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in line with previously reported Aithal et al; Simon et al; Kolata et al (11,15,17). Violent trauma due to fall down from height and vehicle accident were the common causes of fractures as reported previously (2,18). This might be due to most people in our population keep their own dogs on the roof of the buildings and others for playing and jumping.…”
Section: Discussionsupporting
confidence: 63%
“…It often occurs in pet animals due to a trauma, such as jumping from a height or being hit by a vehicle. The severity of the fracture is dependent on the etiology, anatomical locations and age of the animal, which may be hairline, multiple-pieces or compound fractures (2,3). The incidence and percentage could be varied among different animal species, different regions and countries, for instances, in a large veterinary hospital in North America for evaluation of injuries it was recorded that from approximately 35% of dogs and cats were examined, the overall mortality rate was 9% (4).…”
Section: Introductionmentioning
confidence: 99%